Peranan Lembaga Amil Zakat Infak dan Sedekah Muhammadiyah dalam Kesejahteraan Masyarakat: Bukti dari Kalimantan Tengah - Muhammad Riza Hafizi; Putri Mei Ismil Kholifah (Journal of Islamic Social Finance Management, 2021)
This study aims to determine the role of the amil zakat infaq and alms Muhammadiyah institutions in the welfare of society. This research approach uses a qualitative methodology, using qualitative descriptive methods. Qualitative data through semi-structured interviews observation and documentation are also used. Meanwhile, the data validation technique used the source triangulation technique. Data analysis uses the collections, reduction, display, and verification methods. Based on the results of the research that has been done, it is known that LAZISMU's role in the welfare of the community where the fundraising mechanism uses several methods, namely digital fundraising collection, coming directly, direct pick-up, and via transfer. Second, the distribution of ZIS funds is carried out by LAZISMU management assisted by volunteers supported by a database of people who are entitled to receive assistance to simplify the distribution road map. Third, the results of the study found that the socio-economic changes of the community receiving ZIS funds were greatly helped by the assistance that was received, and with the Covid 19 pandemic, LAZISMU management held a Covid 19 alert program. Keywords: Amil Zakat Institution, LAZISMU, Welfare, ZIS, Distribution